The macroeconomic evaluation of transport infrastructure projects - Kampf, Rudolf (Doprava a spoje, 2005)
The article deals with macroeconomic evaluation of transport infrastructure projects and the necessity of all variants comparison. These variants have to be evaluated on the basis of unified key. In common this key may be the Cost - Benefit analysis which means to evaluate infrastructural projects on the basis of comparison of costs and benefits of the construction projects.